INFLUENCER CREDIBILITY AND FOMO IN GEN Z BEAUTY PURCHASES: A CROSS-NATIONAL STUDY (POLITEKNIK LP3I JAKARTA, 2026)
This study investigates how influencer credibility and Fear of Missing Out (FOMO) shape brand attitude and purchase decisions in TikTok beauty marketing among Generation Z consumers in Thailand and Indonesia. A quantitative cross-sectional design was employed with 800 Gen Z TikTok users (400 from Thailand, 400 from Indonesia) who followed beauty influencers. Data were analyzed using PLS-SEM, MICOM, and Multi-Group Analysis. The findings show that attractiveness and expertise significantly enhance brand attitude, with expertise producing the strongest effect (β=0.545). Trustworthiness does not significantly influence brand attitude. Brand attitude and FOMO significantly increase purchase decisions, but FOMO does not moderate the brand attitude-purchase decision relationship. Brand attitude fully mediates the effects of attractiveness and expertise on purchase decisions. Multi-group analysis reveals that expertise and brand attitude effects are stronger in Indonesia, while FOMO effects are stronger in Thailand. The study extends the Theory of Reasoned Action and Social Influence Theory to the TikTok beauty context, demonstrating that expertise-based credibility operates through brand attitude. At the same time, FOMO functions as a direct emotional driver. For beauty brands, expertise-oriented content should be emphasized in Indonesia, while time-sensitive campaigns should be used in Thailand.